Clinical Evaluation of the Enhanced Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test for Rapid Diagnosis of Tuberculosis in Prison Inmates - Bergmann, John S. (American Society for Microbiology, 1999)
The reliability of the enhanced Amplified Mycobacterium Tuberculosis Direct Test (E-MTD; Gen-Probe, Inc., San Diego, Calif.) for rapid diagnosis of pulmonary tuberculosis (TB) was evaluated by testing 1,004 respiratory specimens from 489 Texas prison inmates. Results were compared to those of mycobacterial culture (BACTEC TB 460 and Middlebrook 7H11 biplates), smear for acid-fast bacilli (AFB; auramine O), and clinical course. After chart review, three patients (nine specimens) who were on antituberculosis therapy before the study began were excluded from final analysis. Of the remaining 995 specimens, 21 were AFB smear positive: 13 grew Mycobacterium tuberculosis complex (MTBC), 6 grew nontuberculous mycobacteria, and 2 (from two patients diagnosed with TB and started on therapy after the study began) were culture negative. Twenty-eight specimens (20 patients) were positive for MTBC by culture and E-MTD. Seven specimens (seven patients) were positive by culture alone; three were from patients who had other E-MTD-positive specimens, two were false-positive cultures, and two were false-negative E-MTD results. Eight specimens were positive by E-MTD only; four specimens (four patients) were false-positive E-MTD results, and four specimens were from two patients with earlier E-MTD-positive specimens that grew MTBC. Thus, there were 22 patients with TB (10 smear positive and 12 smear negative). The sensitivity and specificity of the AFB smear for diagnosis of TB, by patient, were 45.5 and 98.9%, respectively. After resolving discrepancies, these same values for E-MTD were 90.9 and 99.1% overall, 100 and 100% for the smear-positive patients, and 83.3 and 99.1% for the smear-negative patients. Excluding the one smear-negative patient whose E-MTD-negative, MTBC culture-positive specimen contained inhibitory substances, the sensitivity of E-MTD was 95.2% overall and 90.9% in smear-negative patients. The specificity and positive predictive value of E-MTD can be improved, without altering other performance characteristics, by modifying the equivocal zone recommended by the manufacturer. These data suggest that E-MTD is a reliable method for rapid diagnosis of pulmonary TB, irrespective of the AFB smear result. Guidelines for the most appropriate use of E-MTD with smear-negative patients are needed.